Climate change and Paris Agreement: A Case Study of Lahore - Munir, Abira; Jathol, Hadia; Nisar, Misbah (Annals of Human and Social Sciences, 2024)
This research examines the climate change as a political problem in Lahore, Pakistan, where environmental degradation and urban challenges worsen with poor governance and socioeconomic inequalities. Consequently, increasing temperatures, air pollution, and heavy metal contamination result from industrial emissions, vehicular pollution, and agricultural burning, bringing about health crises that affect marginalized communities disproportionately and increase inequalities. While international climate frameworks like the Paris Agreement provide a global context, their implementation is minuscule given the lack of political commitment and geopolitical differences. This work employs quantitative methods such as case studies to identify governance deficits and disjointed policy implementation requiring interventions whose focus must be community-specific, localized, and transformational. Therefore, this study would advise applying environmental justice and redistributive policy reforms for sustainable climate resilience strategies that, albeit developed, are fit for other growing urban centers in South Asia.